Medical geography and its contribution to the aetiology of rare systemic connective tissue diseases : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - Borman, Graham Barry (Massey University, 1975)
This thesis is in two interrelated parts. Part One traced the historical development of medical geography since the idea of applying a geographical perspective to medical problems was first mooted in 4 B.C. The main trends in the evolving philosophy and methodology of this field were noted, and a distinction was made between the Western and Soviet interpretations of the nature and scope of medical geography. The methods available to medical geographers for cartographically portraying medical data were discussed. Part Two represented the application cf geographical principles to the study of rare systemic connective tissue diseases. The inherent problems of collection. and of verification of the medical data used in this study were detailed. Using cartographic and statistical techniques the diseases under study were spatially and temporally defined. It was found that scleroderma had a statistically significantly high incidence in the Taieri Geographic County, and it was this disease and this area which wore the principal contributory factors to the statistically significantly high incidence of all connective tissue diseases at the larger scales of areal units in the Otago region. The structures of the populations affected by these diseases were also studied, with the findings generally confirming the results obtained in overseas surveys. No association was found between the incidence of systemic lupus erythematosus, and high sunshine hours, while the disease subsets did not exhibit a rural or urban bias in their incidence. Paucity of cases precluded a study of the possible racial predilection of the diseases or any association of incidence with a patient's occupation. Suggested avenues for possible aetiological research accruing from this analysis were detailed.
Keywords: Medical geography; Connective tissues; Diseases -- Etiology